Bimbingan Kelompok Mengunakan Teknik Cinematherapy Untuk Meningkatkan Pemahaman Kepercayaan Diri Peserta Didik - Sriyani; Sendayu, Fendahapsari Singgih; Suriatie, Mimi (Universitas Palangka Raya, 2024)
Self-confidence is the belief that each individual has in themselves for everything they do. The problem experienced by students is low self-confidence related to belief in their own abilities, optimistic, objective, responsible, rational, brave and able to adjust. The purpose of this research is to see the effectiveness of group guidance services using Cinematherapy techniques to increase the understanding of self-confidence in students in class XI MIPA 6 SMAN 2 Palangka Raya which is still low in the understanding of students related to self-confidence. This research uses experimental research with a one group pretest- posttest design. The population in the study was 50 students and the sample amounted to 6 students. Data collection techniques used questionnaires, interviews, observations, documentation, books, articles, journals. Calculation of normally distributed data, using Kolmogrov-Smirnov parametric statistics and t-test calculations using paired sample t tests with rocks (SPSS Program Version 25). Data analysis using normality test and t-test. with negative hypothesis testing criteria, the t-table value is 22.345 less than 2.015. It can be concluded that group guidance using Cinematherapy techniques is effective for increasing understanding of self-confidence in students in class XI MIPA 6 SMAN 2 Palangka Raya.